Diffusion-weighted imaging in musculoskeletal radiology—clinical applications and future directions - Bhojwani, Nicholas (Quant Imaging Med Surg, 2015)
Diffusion-weighted imaging (DWI) is an established diagnostic tool with regards to the central nervous system (CNS) and research into its application in the musculoskeletal system has been growing. It has been shown that DWI has utility in differentiating vertebral compression fractures from malignant ones, assessing partial and complete tears of the anterior cruciate ligament (ACL), monitoring tumor response to therapy, and characterization of soft-tissue and bone tumors. DWI is however less useful in differentiating malignant vs. infectious processes. As of yet, no definitive qualitative or quantitative properties have been established due to reasons ranging from variability in acquisition protocols to overlapping imaging characteristics. Even with these limitations, DWI can still provide clinically useful information, increasing diagnostic accuracy and improving patient management when magnetic resonance imaging (MRI) findings are inconclusive. The purpose of this article is to summarize recent research into DWI applications in the musculoskeletal system.